Investigation of HgCdTe avalanche photodiodes for HOT condition - Manyk, Tetiana; Sobieski, Jan; Matuszelański, Kacper; Rutkowski, Jarosław; Martyniuk, Piotr (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The performance of long-wave infrared (LWIR) = 0.22 HgCdTe avalanche photodiodes (APDs) was presented. The dark currentvoltage characteristics at temperatures 200 K, 230 K, and 300 K were measured and numerically simulated. Theoretical modeling was performed by the numerical Apsys platform (Crosslight). The effects of the tunneling currents and impact ionization in HgCdTe APDs were calculated. Dark currents exhibit peculiar features which were observed experimentally. The proper agreement between the theoretical and experimental characteristics allowed the determination that the material parameters of the absorber were reached. The effect of the multiplication layer profile on the detector characteristics was observed but was found to be insignificant.